Pengaruh Struktur Modal dan Likuiditas Terhadap Profitabilitas Perusahaan Otomotif di Indonesia pada PT Astra Internasional Tbk - Ermaini Ermaini; Ade Irma Suryani; Endah Tri Kurniasih; Arman Syafa`at; Rian Dani (J-MAS (Jurnal Manajemen dan Sains), 2021)
PT. Astra Internasional Tbk, is a multinational company listed on the Indonesia Stock Exchange from 1990 until now and incorporated in the automotive industry. The covid-19 pandemic made the automotive industry both in Indonesia and in the world weakened by the decline in sales of almost all automotive companies. The focus of this research is to analyze the capital structure of the Debt to Equity Ratio (DER) and liquidity ratio, namely the Cash Ratio (CR) ratio of automotive companies and their effect on profitability, namely the Return on Equity Ratio (ROE) for the period 2016 to 2020 by using secondary data sourced from annual reports published by the company. The results of the study found that the performance of the company's capital structure, liquidity and profitability during 2016 to 2019 had a positive trend and in 2020 decreased as a result of the Covid-19 pandemic outbreak. Furthermore, the ratio of capital structure and liquidity has a positive influence with a significant rate of < 5%.